2016
DOI: 10.21789/22561498.1153
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidad mensual de la velocidad de surgencia y clorofila a en la región del Panama Bight

Abstract: RESUMENLas zonas de surgencia y la presencia de clorofila a en la región del Panamá Bight (golfo de Panamá) fueron comparadas en una escala mensual. Las variables utilizadas fueron la velocidad vertical de surgencia estimada mediante el software EVA. V.2.0 y la concentración de clorofila a obtenida de imágenes satelitales SeaWifs. El estudio fue realizado para el área costera entre 6° 30' y 2° N y en los tres principales focos de ascenso de agua, el primero ubicado entre 83-84° W y 1° 30'-2° 30' N, el segundo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…Zooplankton samples used in this study were obtained during the ERFEN XV-CPC LI oceanographic campaign carried out in September 2012 aboard the ARC Providencia research vessel, ascribed to the Navy National Armed Forces and administered by the Maritime General Direction-DIMAR of Colombia. The oceanographic conditions at this location are strongly influenced by the Panama wind jet and by the intertropical convergence zone (Villegas & Málikov, 2006;Villegas, Málikov & Díaz, 2016). The 21 ºC isotherm occurs between 30 and 35 m depth year-round, and the 15 ºC isotherm occurs at 70 m depth during the first months of the year, and at over 125 m depth during the second semester of the year (Rodríguez-Rubio & Giraldo, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Zooplankton samples used in this study were obtained during the ERFEN XV-CPC LI oceanographic campaign carried out in September 2012 aboard the ARC Providencia research vessel, ascribed to the Navy National Armed Forces and administered by the Maritime General Direction-DIMAR of Colombia. The oceanographic conditions at this location are strongly influenced by the Panama wind jet and by the intertropical convergence zone (Villegas & Málikov, 2006;Villegas, Málikov & Díaz, 2016). The 21 ºC isotherm occurs between 30 and 35 m depth year-round, and the 15 ºC isotherm occurs at 70 m depth during the first months of the year, and at over 125 m depth during the second semester of the year (Rodríguez-Rubio & Giraldo, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It could be that CCS is greatly influenced by local atmospheric and hydrographic processes (Lonin et al 2010, Restrepo et al 2014, generating more differences between the observed SST and the series obtained by ROMS. Instead, the CPB exchanges its waters with the open ocean (Villegas & Malikov 2009) and is influenced by global and regional processes (Wallace et al 1989, Zhang et al 2010, Zheng et al 2012, Villegas et al 2016, which appear to be reflected in the initial, boundary and forcing conditions given to ROMS. Although these factors allowed achieving better results in CPB than in CCS, we have to consider the conclusions of Sierra et al (2018), who evaluated the ability to simulate the ChLLJ of coupled and uncoupled GCMs included in CMIP5.…”
Section: Comparison Between Sst Simulated With Roms In the Recent Past And Observed Data For The Cpb Through Deviation Measuresmentioning
confidence: 99%
“…7b), excluding negative trends observed in the small coastal areas characterized by marked rivers influx from the Andes (Restrepo 2006), positive trends are found throughout the region. Higher positive trends are in 1) the WCSW zone , 2) south of the CPB where oceanic waters (ESW) arrive as part of the NECC (Chaigneau et al 2006), and 3) in upwelling areas observed all year round (Villegas et al 2016) named CCSW. Biasutti et al (2012), when comparing simulations between North American Regional Climate Change Program (NARCCAP) and IPCC AR4 projections, pointed that future climate will resemble an El Niño event, implying weakening of tropical atmospheric circulation in response to warming.…”
Section: Sst Trends In the Colombian Caribbean Sea (Ccs) And Colombian Pacific Basin (Cpb)mentioning
confidence: 99%
“…Este patrón, se ha observado, por ejemplo, al norte de Tenerife (islas Canarias), con aumento de los quetognatos y otros zoopláncteres epipelágicos, por la menor presión depredadora del macrozooplancton y el micronecton (Hernández et al 2001) . Hacia la superficie de la misma región, la biomasa seca del mesozooplancton puede ser muy alta en cuarto creciente y disminuir drásticamente tras luna llena, la que se puede elevar en estratos inferiores, con una gran El análisis de agrupamiento (Figura 4) mostró el asocio de las estaciones de muestreo en cuatro bloques, según los periodos día: noche y las fases lunares, alguna correspondencia con la ubicación de las estaciones en el OPC y los eventos de surgencia, reportados como permanentes para la época de muestreo (Málikov & Villegas, 2010;Villegas et al 2016) .…”
Section: Distribución De Las Biomasas Y Abundanciasunclassified